PRAGMATONYMS. EXTERNAL AND INTERNAL TYPES OF ONOMASTIC CONVERSION (Academicia Globe: Inderscience Research, 2024)
The article discusses the fact that pragmatonyms and their external and internal types of onomastic conversion stylistic play an important role in the formation of brand names.